ARTUR DUCK, DE USU ET AUTHORITATE IURIS CIVILIS ROMANORUM IN REGNO GALLIARUM. PRZEGLĄD BAZY BIBLIOGRAFICZNEJ - Marzec, Łukasz (Zeszyty Prawnicze, 2017)
Artur Duck, De Usu et Authoritate Iuris Civilis Romanorum in Regno Galliarum. The Overview of the Bibliography Summary De Usu et Authoritate Juris Civilis Romanorum in Dominiis Principum Christianorum, the work by Artur Duck was published in London in 1653. Duck, one of the leading civil lawyers, a royalist, high commissioner, Master in Chancery, King’s Advocate and a chancellor of three dioceses wrote his book in exile in Oxford during the English Civil War. In his work he analysed the position and influence of the Roman Law in fourteen countries of 17th-century Europe. The chapter concerning the Kingdom of France deserves a special interest, mainly due to the great number of learned lawyers cited by Duck. His study shows his excellent knowledge of legal works on the French law of that time. This paper tries to present the complete bibliography of the books used by Duck to describe the influence of the Roman Law in the Kingdom of France.